Strategi Humas PT. Tirta Mumbul Jaya Abadi Dalam Membangun Citra dan Reputasi Positif Pada Publik Eksternal - Istri Sinta Sukma Ratih, Cokorda; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2015)
ABSTRACT Tirta Mumbul Jaya Abadi is a company of mineral water (AMDK). This company is a branch of Water Supply Local Company in Buleleng regency(PDAM) which is part of the Regional Owned Enterprises (BUMD). It cooperates with private company, Mara Jaya Dewi Sakti that has been establish in organizational way since 2004.  This water company is quite new in its operation but it has succeded to become the market leader of mineral water in Buleleng regency. It is due to the effort of whole staffs of Tirta Mumbul Jaya Abadi Company especially its public relation. This research applied Image Building and Two Way Symmetrical Model analysing the strategy used by public relation of Tirta Mumbul Jaya Abadi company. It is a descriptive qualitative research that applied triangulation technic in collecting data. This research took place in Singaraja city. The result showed that strategy which was quite effective to be used were publication and public relationship. Public relation of Tirta Mumbul Jaya Abadi Company is active in using electronic and outdoor media as well as maintaing good relationship with their external public through sponsorship effort in both product or financial to build the image of company. Keywords: Strategy of Public Relation, Image, Reputation, PT. Tirta Mumbul Jaya Abadi.